New classes of potent heparanase inhibitors from ligand-based virtual screening - Daniele Pala; Laura Scalvini; Gian Marco Elisi; Alessio Lodola; Marco Mor; Gilberto Spadoni; Fabiana F. Ferrara; Emiliano Pavoni; Giuseppe Roscilli; Ferdinando M. Milazzo; Gianfranco Battistuzzi; Silvia Rivara; et al. (Taylor & Francis Group, 2020)
Heparanase is a validated target in cancer therapy and a potential target for several inflammatory pathologies. A ligand-based virtual screening of commercial libraries was performed to expand the chemical space of small-molecule inhibitors. The screening was based on similarity with known inhibitors and was performed in several runs, starting from literature compounds and progressing through newly discovered inhibitors. Among the fifty-five tested compounds, nineteen had IC50 values lower than 5 µM and some showed remarkable potencies. Importantly, tere- and isophthalamides derivatives belong to new structural classes of heparanase inhibitors and some of them showed enzyme affinities (61 and 63, IC50 = 0.32 and 0.12 µM, respectively) similar to those of the most potent small-molecule inhibitors reported so far. Docking studies provided a comprehensive binding hypothesis shared by compounds with significant structural diversity. The most potent inhibitors reduced cell invasiveness and inhibited the expression of proangiogenic factors in tumour cell lines.